Spectrum of Diabetes Research does not Reflect Patients’ Scientific Preferences: A Longitudinal Evaluation of Diabetes Research Areas 2010–2013 vs. a Cross-sectional Survey in Patients with Diabetes - Arnolds, S.; Heckermann, S.; Heise, T.; Sawicki, P. T. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Objective: To compare the proportions and trends in the distribution of research topics as presented during the annual meetings 2010–2013 of the European Association for the Study of Diabetes (EASD) to patients’ preferences.Methods: Longitudinal evaluation of EASD research areas 2010–2013 divided into 9 main categories and compared with a cross-sectional survey in 918 people (652 with patients with diabetes, 205 relatives, 61 others interested), who had allocated their preferences to the same 9 topics.Results: “Development, pathophysiology and prevention of diabetes” was the primary category of interest for 25% of patients, 19% preferred “transplantation and cell therapy” and 16% “blood glucose measurement, devices and artificial pancreas”. During the 4 years of abstract investigation 50% or more of total research activities was constantly dedicated to “pathophysiology and prevention of diabetes”, less than 2% to “transplantation and cell therapy” and 2.8–4.3% to “blood glucose measurement, devices and artificial pancreas”. The average proportion of EASD research related to “blood-glucose lowering therapy without insulin” and “insulin therapy” corresponded with the proportion of research patients would like to see (12.0 vs. 12.5%, and 6.9 vs. 4.7%, respectively). The majority, however, was commercially funded. Non-commercial research was not closer correlated to patients’ preferences.Conclusion: The distribution of research topics over the last 4 years as measured by the distribution of accepted EASD abstracts does not reflect what patients and their relatives want to have investigated. Better patient involvement and a reassessment of non-commercial funding strategies might help create more valuable research.
Keywords: diabetes; patients’ diabetes research preferences; European diabetes research activities